Invest My Idea: A Case Study of Crowdfunding for Startups and Entrepreneurs in the Kurdistan Region of Iraq - Rebean Al-Silefanee; Dilsher Hatim Ismael (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: This qualitative study explores the effectiveness of crowdfunding as a financing alternative for startups and entrepreneurs in the Kurdistan Region of Iraq (KRI), compared to traditional funding sources such as bank loans and grants. Specifically, the study examines the Invest My Idea initiative by Rwanga Foundation, which supports small businesses and startups throughout Iraq. The research aims to evaluate entrepreneurs' knowledge and experience with crowdfunding, identify barriers to promoting campaigns in KRI, and provide recommendations for future efforts. Design/methodology/approach: Data were gathered through online interviews with four experts and ten entrepreneurs, analysed using thematic analysis. Findings: Findings indicate that crowdfunding holds potential as an effective fundraising strategy for KRI entrepreneurs, contributing to the growth and development of the entrepreneurial ecosystem. Research limitations/implications: However, various obstacles were identified, including lack of trust, cultural barriers, limited knowledge about crowdfunding, legislative issues, and insufficient government support for online campaigns. Practical implications: To address these challenges, the study recommends raising awareness among stakeholders, implementing policy support, and promoting crowdfunding as a widely recognized fundraising method. This research offers valuable insights into the potential advantages and challenges of crowdfunding for KRI startups and entrepreneurs, presenting practical recommendations to enhance campaigns and foster entrepreneurial ecosystem growth. Paper type: Research paper